Productivity of trees and crops under integrated nutrient management in poplar-based agroforestry system - Singh, Baljit; Kaur, Naveent; Gill, RIS; Singh, Jagmanjot (Indian Journal of Agroforestry, 2023)
An experiment was conducted to evaluate the effect of integrated nutrient management on tree and crop productivity in poplar-based agroforestry system from 2012 to 2019 at PAU Ludhiana. The treatments comprised of two tree spacings (5 x 3 m and 4 x 3 m) and 7 nutrient combinations i.e. T1: 75% of recommended NP to sole crops (all inorganic); T2: 75% of recommended NP (50 % N through inorganic source + 50% through FYM); T3: recommended NP (all inorganic); T4: recommended NP (50% N through inorganic source + 50% through FYM); T5: 125% of recommended NP (all inorganic); T6: 125% of recommended NP (50% N through inorganic source + 50% through FYM) and T7: uncropped trees. Wheat was grown from first year till sixth year in rabi season, while maize during 2nd and 3rd year and cowpea during 4th year of tree growth in kharif season. The tree growth parameters (diameter at breast height and height), grain yield of wheat and fodder yield of maize and cowpea were significantly higher in 5 x 3 m than 4 x 3 m spacing during different years of tree growth. The yield of crops increased significantly with increase in level of nutrients from 75% of recommended to 125% of recommended dose of nutrients. The tree growth parameters, crop yield and soil properties (soil OC, available N and P) were relatively higher under combination of organic and inorganic source of nutrients than in inorganic source of nutrients alone. Soil properties were significantly higher in 4 x 3 m spacing than 5 x 3 m after 6 years. Therefore, combination of organic manure and inorganic source of nutrients was better in improving the crop yield and soil properties than inorganic source alone in poplar-based agroforestry system.